The Effect of Marketing Mix on Consumer Satisfaction at UD. Darma Suci Wholesale in Denpasar - Ni Kadek Ayu Surya BINTANG; Ni Made WAHYUNI; Putu Indah HAPSARI (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This study was conducted to investigate the role of the marketing mix on customer satisfaction at UD. Darma Suci Grosir Denpasar. The target population includes a total of 75,270 people.Methodology:Through sampling, 99 consumers participated in the study. Empirical data were obtained using a questionnaire and then analyzed using a multiple linear regression approach.Findings:The research findings confirm that product, price, place, and promotion have a positive and significant relationship, both partially and simultaneously, with customer satisfaction at UD. Darma Suci Grosir Denpasar. Suggestions include the importance of improving product quality and variety, establishing pricing strategies that align with consumer purchasing power, operating in strategic locations, and marketing products online through social media platforms.Implication:This study contributes positively to the marketing management literature and practically to UD. Darma Suci Grosir Denpasar is improving its marketing mix strategy to create highly satisfied customers. This study also guides future researchers to examine other determinants that influence customer satisfaction.